The Mediating Role of Quality Leadership in Lean Practices and GLCs Performance - Mohd Rizal Razalli; Hartini Ahmad; Darwina Arshad (International Journal of Supply Chain Management, 2017)
Lean practices are expected to eliminate wastes and consequently increase the bottom line profit of an organization. The benefits not only go to the organization, but also to the customers as well. The government-linked companies (GLCs) are always known for their big-sized establishment. Hence, managing the resources of the GLCs is very challenging. Therefore, investigating the leanness of Malaysian GLCs, and how lean practices affect the organizational performance are important. This paper would examine the relationship of lean and performance of the GLCs in Malaysia. A total of 281 managers in the GLCs were surveyed. The direct relationship and mediation effects were analysed using the Partial Least Square (PLS) structural equation modelling. The findings showed that the level of leanness was relatively high among the GLCs, while the lean management practice was significantly related to the organizational performance. The quality leadership partially mediates the relationship between lean practices and organizational performance. The findings suggest that lean practices are critical for the GLCs performance, while quality leadership is significant in order these companies to have better performance. The findings can also be applied to other organizations as well.